POST-VARISCAN MAFIC DIKES FROM THE LATE OROGENIC COLLAPSE TO THE TETHYAN RIFT: EVIDENCE FROM SARDINIA - Gaggero, Laura; Oggiano, Giacomo; Buzzi, Laura; Slejko, Francesca; Cortesogno, Luciano (Ofioliti, 2007)
Dolerite dikes cut the Lower Paleozoic medium- to high-grade metamorphic basement, the Sardinia-Corsica batholith and the Stephanian - Autunian calcalkaline effusives (1st volcanic episode, according e.g. to Bonin, 1989; Cabanis et al., 1990) with a N-S trend and subvertical dip. Their occurrence is reported from several areas of Sardinia, from the N to the SE. The basic dikes are associated with diorite to rhyolite dikes having trends ranging from E-W to N-S. A late Triassic lamprophyric dike intruded the garnet-staurolite-kyanite micaschists near Mt. Nieddu and has a 40°N direction. Two 40Ar-39Ar age determinations for the dolerite dikes were carried out on amphibole. Ages between 253.8±4.9 and 248±8 Ma (Permian - Early Triassic) probably correspond to the emplacement interval.A continental within-plate geochemical signature, with prevalent tholeiitic to transitional (dolerites) and minor alkalic (lamprophyre) terms, has been determined. The relative LILE and REE enrichment compared with the MORBs and Nd isotopic ratios (4 bulk samples; initial 143Nd/144Nd ratios between 0.512529±0.000025 and 0.513143±0.000023) is consistent with a source in a sub-continental lithospheric mantle. The remarkable compositional and isotopic variability can be explained by the partial melting of a heterogeneous source. Crustal contamination variably affects some transitional dikes; the host Arzachena monzogranite probably represents the major contaminant source.On the whole, the geochemical data support an anorogenic geochemical affinity, in accordance with the extensional regional tectonics, for the Permo-Triassic dikes in Sardinia. The E-W emplacement patterns correspond to the major fractures and primarily R and RI structures associated with the late Variscan transcurrent-extensional E-W faults. The N-S emplacement trend is consistently associated with a generalized E-W extension of the Sardinian crust: in a predrift restoration it coincides with the patterns of extension between the European and Insubric crust at the beginning of the Tethyan rift.In Sardinia, the lamprophyre dike is significantly younger than the late Variscan alkaline volcanites and dikes of the rest of the Mediterranean domain (e.g. Eastern Provence: 278-264 Ma, 40Ar/39Ar isotope dating on feldspar from rhyolites and on plagioclase from mafic flow, Zheng et al., 1992; Western Pyrenean Axial Zone: 271-266 Ma, K-Ar isotope dating on kaersutite phenocrysts from mafic dikes, Debon and Zimmermann, 1993), in accordance with the diachronism of both the first and second volcanic episodes in different areas of the Mediterranean domain. The overlap between the calc-alkaline events and the volcanic and sub-volcanic alkalic event, is not exclusive to Sardinia and Corsica (e.g. the Pyrenees and Pan-African orogen).